تقييم استخدام مسحوق الريش كمصدر للبروتين الغذائي لصغار سمك الكارب العادي(Cyprinus carpio L.) - منصور, كاترين (Latakia University Journal -Biological Sciences Series, 2019)
This study aimed at investigating the effect of hydrolyzed feather meal on the growth performance and survival of Cyprinus carpio fry. Four isonitrogenous (45 % protein and 600 kcal GE/100g) diets were tested, the first with fish meal as a major protein source, the second contained a mixture of fish meal and hydrolyzed feather meal, while the third one contained hydrolyzed feather meal as a major protein source, and the last diet contained a mixture of hydrolyzed feather meal and soybean meal. The common carp fry were fed three times a day to satiation for 21 days. The results showed that the first diet produced the best performance, and significant differences (P<0.05) were found compared to the other diets, the worst results were found in the third diet, while the growth was better using the second and the fourth diet compared to the third one. Survival rate was not affected (P>0.05) by the first, second and fourth diets, while the mortality of fry was important using the third diet. أجري هذا البحث لدراسة تأثير اضافة مسحوق الريش كمصدر للبروتين على مظاهر النمو والبقاء على قيد الحياة لصغار سمك الكارب العادي Cyprinus carpio. تم تحضير أربع خلطات علفية احتوت على نسبة واحدة من البروتين ( 45 % و 600 كح/100 غ عليقة) حيث احتوت الخلطة الأولى مسحوق السمك كمصدر رئيس للبروتين، بينما تضمنت الثانية مزيج من مسحوق السمك و مسحوق الريش، واحتوت الثالثة مسحوق الريش كمصدر أساسي للبروتين وتكونت الخلطة الأخيرة من مزيج من مسحوق الريش و مسحوق فول الصويا. غذيت صغار الكارب بمعدل ثلاث مرات في اليوم حتى الشبع لمدة 21 يوما". أشارت النتائج أن أفضل معدلات للنمو و معامل تحويل الغذاء تم الحصول عليها من الصغار التي علفت على الخلطة الأولى، حيث وجدت فروق معنوية (P<0.05)بين نتائج هذه الخلطة و الخلطات الأخرى، في حين أعطت الخلطة الثالثة أسوأ النتائج, بينما تحسن الأداء لحد ما عند استخدام الخلطتين الثانية و الرابعة بالمقارنة مع الثالثة (P<0.05). كما دلت النتائج على أن معدل البقاء على قيد الحياة (P>0.05) لم يتأثر بمصادر البروتين في الخلطات الأولى، الثانية والرابعة بينما كانت نسبة النفوق عالية عند الصغار التي علفت على الخلطة الثالثة.